Neuroplasticity in Alzheimer's disease: a therapeutic alternative at the molecular level - Noel Jesús Niebla Gómez; Rodolfo Javier Rivero Morey; Víctor René Navarro Machado; Mariangel González León; Amanda Martínez Pérez (Medisur)
The neuroplasticity mechanisms of the organism form the basis of dissimilar therapies that seek to potentiate such effects to achieve relative improvement in a large number of neurodegenerative diseases. Included within this high number of conditions, Alzheimer's disease stands out, due to its direct relationship with the alarming figures of population aging in Cuba and the world. The objective of this bibliographic review was to describe the main therapeutic alternatives that are based on the neuroplasticity mechanism, applicable in patients with Alzheimer's disease. For this, a literature review was carried out, and relevant publications from the last five years were identified. It was concluded that, according to the strongest evidence found, the fundamental therapeutic alternatives are those focused on enhancing neuronal plasticity; standing out within this group of therapies, physical exercise, transcranial magnetic stimulation and increased concentrations of brain-derived neurotrophic factor. Especially notable the repetitive transcranial magnetic stimulation, due to its demonstrated ability to promote neuronal plasticity through different ways.